Analisis Kepuasan Self Monitoring Blood Glucose Dengan The Glucose Monitoring Satisfaction Survey - Shanty Chloranita (Jurnal Kesehatan Panca Bhakti Lampung (JKPBL), 2020)
The satisfaction self monitoring of blood glucose is an important factor in improving diabetes outcomes type 2 diabetes patients. The application of evidence based nursing aims to identify the satisfaction self monitoring of blood glucose in type 2 diabetes patients. Problem formulation method used by the problem approach (P) intervention (I) comparison (C) outcome (O), and literature search with a sample of 51 type 2 diabetes patients. The measuring instrument used is the glucose monitoring satisfaction survey (GMSS). Analysis shows the average of respondents in this study was 65% of respondents with a total score of 49.43. The glucose monitoring satisfaction survey conclusion can be applied.